Long-term impact of COVID-19 associated acute respiratory distress syndrome. Issue 5 (November 2021) - Aranda, Judit; Oriol, Isabel; Martín, Miguel; Feria, Lucía; Vázquez, Núria; Rhyman, Nicolás; Vall-Llosera, Estel; Pallarés, Natàlia; Coloma, Ana; Pestaña, Melani; Loureiro, Jose; Güell, Elena; et al.
Highlights: Most COVID-19 associated ARDS survivors have persistent symptoms beyond 8 months. At 8 months, COVID survivors with ARDS often have decreased exercise capacity. Almost all COVID survivors with ARDS develop at least one mental disorder. Female sex, non-Caucasian race, and Charlson>2 were risk factors for a worse MCS score on the SF-36. Female sex and COPD were independent risk factors for a worse PCS score on the SF-36. Abstract: Objectives: To determine the health status, exercise capacity, and health related quality of life (HRQoL) of COVID-19 associated acute respiratory distress syndrome (ARDS) survivors, 8 months after diagnosis. Methods: All eligible patients were interviewed and underwent a physical examination, chest X-ray, and 6 min walk test (6MWT). Scales to evaluate post-traumatic stress disorder, depression, anxiety, and HRQoL were applied. Results: Of 1295 patients, 365 suffered ARDS and 166 survived to hospital discharge. Five died after discharge and 48 were lost to follow-up. Of the 113 remaining patients, 81% had persistent symptoms. More than 50% of patients completed less than 80% of the theoretical distance on the 6MWT, 50% had an abnormal X-ray and 93% of patients developed psychiatric disorders. Mean SF-36 scores were worse than in the general population. After multivariate regression analysis, female sex, non-Caucasian race, and Charlson index>2 were independent risk factors for a worse mental health component summary score on the SF-36, and age was associated with a better prognosis. Female sex and chronic obstructive pulmonary disease were independently associated with a worse physical component summary score. Conclusion: COVID-19 associated ARDS survivors have long-term consequences in health status, exercise capacity, and HRQoL. Strategies addressed to prevent these sequelae are needed.